A Proletarian Prometheus: Socialism, Ethnicity, and Revolution at the Lakehead, 1900-1935 - Beaulieu, Michel S. (Queen's University, 2007)
[Analyzes] various socialist organizations operating at the Canadian Lakehead (comprised of the twin cities of Port Arthur and Fort William, Ontario, now the present-day City of Thunder Bay, and their vicinity) during the first 35 years of the twentieth century. It contends that the circumstances and actions of Lakehead labour, especially those related to ideology, ethnicity, and personality, worked simultaneously to empower and to fetter workers in their struggles against the shackles of capitalism. The twentieth-century Lakehead never lacked for a population of enthusiastic, energetic and talented left-wingers. Yet, throughout this period the movement never truly solidified and took hold. Socialist organizations, organizers and organs came and went, leaving behind them an enduring legacy, yet paradoxically the sum of their efforts was cumulatively less than the immense sacrifices and energies they had poured into them. Between 1900 and 1935, the region's working-class politics was shaped by the interaction of ideas drawn from the much larger North Atlantic socialist world with the particularities of Lakehead society and culture. International frameworks of analysis and activism were of necessity reshaped and revised in a local context in which ethnic divisions complicated and even undermined the class identities upon which so many radical dreams and ambitions rested.
https://qspace.library.queensu.ca/bitstream/1974/1715/1/Beaulieu_Michel_S_200712_PhD.pdf
Keywords: 1900-1935; Canada; Communist Party of Canada; Ethnicity; Finns in Canada; Fort William; Ontario; Industrial Workers of the World; Labour history; Lakehead; Northwestern Ontario; One Big Union; Port Arthur; Ontario; Radicalism; Revolution; Social Democratic Party of Canada; Socialism; Socialist Party of Canada; Winnipeg general strike

La domesticité dans la colonie laurentienne au XVIIe siècle et au début du XVIIIe siècle (1640-1710) - Bessière, Arnaud (Université du Québec à Montréal et Université Paris IV - Sorbonne, 2007)
Cette thèse porte sur les domestiques au Canada entre 1640 et 1710. Recrutée en France ou dans la colonie, cette main-d'oeuvre, principalement masculine, est au service des paysans propriétaires et des communautés religieuses. Ses fonctions sont donc surtout liées à l'agriculture : défrichements, culture des terres, soin du bétail. Mais cela n'exclut pas des tâches comme le soin des malades et l'entretien ménager pour les communautés religieuses et les employeurs urbains plus fortunés. Au fil des ans, la composition du groupe se modifie : les domestiques sont de plus en plus d'origine canadienne et de plus en plus jeunes. Cette évolution est certes à rapprocher de la baisse du mouvement migratoire vers la colonie qui était en grande partie formé de domestiques. En plus d'analyser les modalités d'embauché, la thèse aborde la question des relations entre les maîtres et les domestiques et tente de cerner le devenir social du groupe dans la colonie.
https://cha-shc.ca/prize-winner/arnaud-bessiere/
Keywords: Canada; Domesticité; Domestique; Employeur; Engagé; Immigration; Main-d'œuvre; Maître; Nouvelle-France; Salaire; Servante; Serviteur; XVIIe siècle.

British Juvenile Immigrants in Canada 1868 to 1939: A Study of the Relationship Between Societal Changes and the Treatment of Home Children - Coombes, Brianna Leigh (Ryerson University, 2007)
This paper examines the history of the British juvenile immigrants, a group of over 100,000 children who arrived in Canada between 1868 and 1939 to work on farms or as domestic workers. There was both a pressing need within Canada for farm workers, and overcrowding in British cities, therefore conditions were right for a mutually beneficial labour exchange between the two nations. British philanthropists encouraged this movement and ensured its continued success over a seventy year period. The societal changes that occurred in Canada during the same period as a result of the reform movement are also traced within this historical examination. The increase in child welfare policies, and the subsequent attitudinal changes in the Canadian public also impacted how the home children were treated and viewed. Through this research, this neglected group of immigrants will be given a more prominent position in Canadian social and immigration history.

Chameleons, Chimeras and Shape-Shifters: The Production of Neoliberal Government in Ontario - Coulter, Kendra (University of Toronto, 2007)
Drawing on data from a sixteen-month ethnography of Queen’s Park, the provincial legislature of Ontario, this study analyses and critiques the evolving production of neoliberal government. The work of real social actors, primarily political workers and politicians, and their active ideological and material creation of government, is central to my focus on the neoliberal project of the Liberal government in Ontario. After charting the historical trajectory of neoliberalism internationally and in Canada, with a particular emphasis on the Third Way approach, Icentre on thedevelopment of neoliberal political culture and restructuring in Ontario. Then I provide an in-depth analysis of the production of the Liberal government, focusing on social and fiscal policies and policy-making, hegemonic gender and class politics, and political communications and spin. I conclude that, at one level, the Liberal chimera fused certain progressive practices and language with neoliberal policies and rhetoric. At the same time, significant and dangerous initiatives that interlocked the public and for-profit sector conceptually and materially were pursued. Thus, a more camouflaged form of deep neoliberal integration was produced.
OCLC: 664421107
Keywords: Academic Dissertation; Academic theses; Thèses et écrits académiques

Labour Goes to War: The CIO, the People's War, and the Construction of a "New Social Order," Toronto, 1939-1945 - Cuthbertson, Wendy Elizabeth (University of Toronto, 2007)
The CIO related this narrative to working-class Canadians through new, union channels of communication and through a myriad of union-minded social interactions. Together - the CIO's narrative of victory and its subaltern public sphere that communicated this narrative - helped the CIO overcome formidable obstacles to organizing. The Canadian CIO's 1930s momentum had stalled by 1939, but by 1944 it was the country's largest labour organization and was influencing Canadian politics. Using union newspapers, organizing literature, minutes, correspondence, oral interviews, government and corporate records, and the daily press, this dissertation describes and analyzes how the CIO organized thousands of wartime workers into unions in spite of significant obstacles. This study then examines the institutions the CIO developed to create a union "mini-public sphere," where workers debated and developed union positions on issues facing them as workers, family members, citizens and military veterans. The CIO was successful in turning private, workplace issues such as union recognition and bargaining rights into public issues that government was forced to deal with, and its organizing successes and its entry into politics witnessed burgeoning support for the social democratic CCF, a phenomenon that encouraged mainstream political parties to adopt more progressive platforms. The CIO's breakthrough was based not just on worker-empowering wartime labour shortages. Its skill in using modern communications was also a factor in its wartime success, as well as its use of the war as a central character in these communications efforts. CIO communications used a narrative that elided workers with warriors as partners in a "people's war" to defeat the nation's enemies and build a new social order. The CIO told workers that if they organized into unions, they would have the power to shape a peace that, unlike after the Great War, would benefit this worker-warrior partnership. Victory was thus defined not merely as defeating the Axis but creating a modern, new Canada, where workers would have citizenship rights in the workplace and where citizenship entailed a fairer, more egalitarian society. The CIO's talk about rights extended to women workers, and its arguments for equal pay and women's seniority were increasingly based on women's human rights.

The Split in the AFL-CIO: Implications for the Canadian Labour Movement - Declerck, Sarah (McMaster University, 2007)
In July 2005, six unions withdrew from the central labour federation in the United States, the AFL-CIO. In September 2005, joined by a seventh union, the disaffiliated unions formed a rival labour federation called Change to Win (CTW). On the surface according to Stem, leader of the CTW coalition, what divides the two sides of the split is a disagreement over whether or not to place greater emphasis on organizing new members or altering the political climate in the US in order to facilitate orgamzmg. This thesis explores some of the earlier debates within the union renewal literature in the US and in Canada and exposes many ofthe similarities between the 1995 "New Voices" leadership ofthe AFL-CIO and the CTW leadership. Through a description and analysis of the events that led to the split in the AFL-CIO, the limitations ofthe debates that led to the split are revealed and the strategies for union renewal advanced by the proponents of CTW are critiqued. Drawing on interviews with elected leaders and staff from some of the Canadian sections of the CTW unions, one of the largest Canadian unions, the Ontario Federation of Labour and the Canadian Labour Congress, this thesis examines some of the implications of the split in the AFL-CIO on the Canadian labour movement. As trade unionists in Canada consider different approaches to union renewal, one option is to embrace an approach similar to the CTW approach: greater cooperation with employers and a more "efficient" business unionism. Another approach is union renewal with a socialist character; developing working-class capacities to construct socialist alternatives and renew the labour movement as an instrument of working-class struggle.

Les accidents mortels en milieux de travail dans le district judiciaire de Montréal de 1890 à 1930 : recension et analyse à partir des rapports d'enquête des coroners - Dionne, Jean-Claude (Université de Montréal, 2007)
L’objet de ce mémoire est la recension et l’analyse des accidents mortels survenus dans les milieux de travail du district judiciaire de Montréal durant la période de 1893 à 1930. À partir des témoignages contenus dans les rapports d’enquête des coroners, nous analyserons les opinions des travailleurs, des contremaîtres, des coroners et des inspecteurs afin de connaître leur point de vue sur les accidents et de vérifier dans quelle mesure ils partagent les valeurs libérales de cette époque. Pour constituer notre corpus d’information, nous avons dépouillé chacun des 1527 dossiers des rapports d’enquête des coroners effectuée entre le premier janvier 1893 et le 31 décembre 1930. Ils constituent notre principale source à partir de laquelle nous établirons l’ampleur des accidents mortels et également analyserons les témoignages recueillis par les coroners, Pour fin d’analyse, nous avons réparti ces données sous les quatre décennies couvertes par notre étude et élaboré des tableaux statistiques établissant la distribution annuelle et décennale de ces accidents de même que l’âge et le sexe des victimes. Nous avons également distribué ces accidents par secteurs d’activités économiques et par catégories d’accidents. Si les employeurs, les contremaîtres et les inspecteurs des manufactures adhèrent aux principes de l’idéologie libérale de l’époque en attribuant aux travailleurs la responsabilité première des accidents de travail, les coroners et les travailleurs considèrent, par contre, dans une forte proportion (72 %) que les causes de ces accidents sont associés à des défaillances des divers éléments des lieux de travail et aux processus de production. Ils sont donc plus enclins à attribuer la responsabilité aux employeurs.
https://doi.org/1866/17912

[e]motions, Moments, and Transnational Connections: The Lived Experiences of Two Labour Migrants in Canada's Seasonal Agricultural Workers' Program - Ferguson, Nelson (Concordia University, 2007)
Labour migrants have been routinely categorised within social scientific thought as either abstracted economic entities or as victims of global processes beyond their understanding. A striking majority of attempts to understand processes of migration, especially in regards to "unskilled" Mexican migrant workers, have been informed primarily by macro-level economic approaches, while the social and individual factors at play have been largely pushed to the side. As such, the social lives and individual diversities of these migrants have received meagre academic attention. In acknowledgment of this gap, this current thesis focuses on the lived experiences of Hector-Alberto and Durango, two individuals engaged in a cycle of migration as participants in Canada's managed migration program, the Seasonal Agricultural Workers' Program. Through an ethnographic description of the everyday experiences of Hector and Durango, three relevant themes are explored: their individual relations to their work, their family, and their co-workers. As such, the present work aims to explore the varied experiences of migration and frame labour migrants as significant social actors rather than abstracted units or victims of social forces. The author encourages an engagement in a broader investigation of the "migrant experience"; to look beyond the idea of transnational migration as simply physical movements across national boundaries, but rather as groupings of processes with profound and diverse meanings to those involved. Perhaps such a perspective would play a role in revealing the complex myriad of interacting processes which combine under the umbrella term of "migration".
Keywords: Social sciences

The Working Class After the Vanguard: Process and Plurality in the Theory and Practice of Working Class Organization - Green, Brian Stephen (University of British Columbia, 2007)
This thesis examines what the two sides of class– capital and working class –have meant in left parlance, what these meanings imply about class struggle, and how they were put into political practice through Communist Parties and trade unions. Ideas about class and strategies for class struggle continue to be central to the left, as the various ways these are conceptualized give rise to very different answers to some common and persistent questions: Who is legitimately a worker and when? Why, how and with what result are certain struggles delayed or subsumed within others? At what point does self-criticism cross over to counter-revolutionary dissent? And what might continuing schisms over these questions tell us about traditional left organizations? The thesis traces the development of 'the left' from its key conceptual subject, the working class, through its two most widely-adopted organizational strategies in order to examine the poverty of the left's analytical and political traditions, particularly as regards (1) the notion of socialism as an alternative management plan and (2) ideas about capital and working class that stressed the embodiments of power relations rather than those relations themselves, and which were lifted directly from capital's own definitions of productivity. Finally, the thesis argues that insights from long-neglected Marxisms, certain critical post-structuralisms and the political strategies of some emergent anti-capitalist networks together offer the opportunity to produce a more fluid, and more liberatory left, imbued with: (1) an understanding of class as a relationship that does not inhere to individuals or organizations, and (2) a notion of the working class as a permanent resistance that has nothing whatever to do with a particular ideology or strategy; with (3) an analysis which emphasizes situational relationships of power that are at once racialized, gendered, sexualized, and classed; and (4) a political approach which draws means and ends together in an emphasis on resistance as the troubling of order, and revolution as a process of refusal.

"The Both of Us Have Battled": The Practices and Politics of Female Partners in the Canadian Seasonal Agricultural Workers Program - Hanson, Christina (Simon Fraser University, 2007)
Through an analysis of qualitative, ethnographic data, I locate the narratives of nine Mexican women married to migrants within the context of capitalist globalization, state policies, and local gender ideologies. In doing so, advocate for a theoretical approach to migration which combines elements of structural theories of migration and network theoretical approaches. These women's narratives position them at the juncture of capitalism and other social relations, and show them to be active agents in migration. Not only is their labour critical to the maintenance of migration patterns and the capitalist relations into which migrants and non-migrants are incorporated, but women's labour is also imbued with social meanings.
Keywords: Canada – Mexico – Migration; Canadian Seasonal Agricultural Workers Program; Gender and migration; Mexico – Emigration and Immigration – Social Aspects – Case studies; Non-migrating women and globalization; Seasonal Agricultural Workers Program (Canada); Social aspects of migration; Temporary foreign worker programs; Women – Mexico – Social Conditions

Plus ça change? A Comparative Analysis of the Seasonal Agricultural Workers Program and the Pilot Foreign Worker Program for Farm Workers in Quebec - Lowe, Sophia J. (Ryerson University, 2007)
For the last 40 years, migrant farm workers from the Caribbean and Mexico have been recruited to work temporarily on Canadian farms under the Seasonal Agricultural Workers Program (SAWP). In 2002, the pilot Foreign Worker Program (FWP) for low skilled migrant workers was initiated in the province of Quebec and under this program began the recruitment of Guatemalan migrant farm workers. Since the program's start, the number of Guatemalan migrants has nearly tripled and there seems to be a decline in the number of workers hired under the SAWP in Quebec. This paper examines the FWP's development, set-up, consequences and operation alongside the SAWP and shows how the Canadian state is expanding the number and flexibility of temporary worker programs. This paper draws attention to the neo-liberal context of migrant farm labour in Canada, pointing to the ways in which Canada's federal policies governing seasonal agricultural migrants and the agricultural labour market are exploitative and racist.
Keywords: Foreign Worker Program; Migrant; Seasonal Agricultural Workers Program; easonal; foreign labour; racism; temporary

Fast Food Alienation: Service Work and Alienation in British Columbia, 1968-1998 - Milloy, Jeremy Strachan (Simon Fraser University, 2007)
Since World War II, service work has become the major employment sector in North America. One of the most recognizable forms it takes is in the fast food industry, a multi-billion dollar business with outlets all over the globe. Little has been written about the history of this work, central to the functioning of the global economy and a key part of the move from an industrial economy to a consumer one. This move has changed work by examining BC's White Spot chain, which unlike almost any other has been unionized for over three decades. Drawing on union records an d oral interviews, it analyzes fast food unionism, evaluates organizing in the sector, and draws out workplace dynamics and processes; arguing that labour practices in this sector have been crucial in making work more exploitative.

The Empire Within: Montreal, the Sixties, and the Forging of a Radical Imagination - Mills, Sean William (Queen's University, 2007)
This thesis explores the wide variety of ways in which radical intellectuals and activists in Montreal used and adapted Third World decolonization theory to build a broad movement of solidarity and anti-colonial resistance from 1963-1972. Beginning in the early 1960s, activists and intellectuals in Montreal began drawing upon the language of Third World decolonization to resituate their understandings of themselves, their society, and the world in which they inhabited. Through their engagement with Third World liberation theory – and the closely related language of Black Power – radical intellectuals in Montreal sought to give new meaning to the old conception of humanism, and they worked to drastically expand the geographical frame of reference in which Quebec politics were generally understood. After analyzing the shifting meaning of decolonization in the period leading up to the late 1960s, this thesis explores the ways in which various groups adopted, built upon, challenged, and shaped the conception of Quebec liberation. Montreal’s advocates of women’s liberation, the city’s Black activists, defenders of unilingualism, and labour radicals were all deeply shaped by the intellectual and urban climate of Montreal, and by ideas of Quebec decolonization. They developed their own individual narratives of liberation, yet linked by the flexible language of decolonization, these narratives all greatly overlapped, forming a vast movement which was larger than the sum of its parts. If the concept of decolonization was extremely powerful, however, it was also highly ambiguous and contradictory, and activists only slowly came to an understanding of the multi-layered nature of colonialism in Quebec. By the early 1970s, the idea of decolonization was slowly abandoned by those advocating radical social change in the city. This thesis makes three interrelated arguments. First, it argues that radicalism in Quebec in the 1960s cannot be understood outside of the larger international context in which it emerged. Second, it attempts to rethink the ways in which different groups and movements during the 1960s interacted and fed upon each other’s analyses and learned from each other. And, finally, by looking at the centrality of Third World decolonization to the development of dissent in Montreal, it hopes to add new perspectives to the growing field of international Sixties scholarship, by insisting that history of the ‘West’ was profoundly shaped by its interactions with the Third World.

Women's Experiences and Representations of Diversity Management and Organizational Restructuring in a Multinational Forest Company - Mills, Suzanne Elizabeth (University of Saskatchewan, 2007)
This thesis examines the relationship between worker identity and workplace practices from the perspectives of white and Aboriginal women working in a multinational forest company in the northern prairies. Over the course of three manuscripts I demonstrate the salience of ascribed and constructed identities of women to their experiences and representations of forest employment and corporate discourse. Setting the context for the remainder of the thesis, the first manuscript presents an analysis of employment segregation by gender and Aboriginal identity in Canada’s forest sector in 2001 using segregation indices. Results demonstrate that forest employment was vertically segregated by both gender and Aboriginal ancestry in the forest sector in 2001. Men and women of First Nations ancestry were over represented in less-stable and lower paying occupations in woods based forest industries, and both white and First Nations women were over represented in forest services and clerical occupations. To explore women’s perceptions of company practices of diversity management and restructuring, I then analysed interviews with women working in forest processing using critical discourse analysis. In my second manuscript, I demonstrated how women’s representations of diversity management practices were linked to their social identities in terms of Aboriginal identity and class. Yet, as a whole, these representations prompted a questioning of the meaning of difference within diversity management, and of diversity management’s ability to further the interests of marginalised workers. My third manuscript examining representations of restructuring, argues that there is a two way relationship between women’s identities as workers and their representations of restructuring. Whether women reproduced or resisted restructuring was linked to their presented work identities and restructuring and practices in turn were helping to shape women’s worker subjectivities. Results from this thesis demonstrated that how women represent themselves and workplace practices is related to their different experiences in the specific set of social relations of forestry work in the northern prairies.

Constituting Authority: Policing Workers and the Consolidation of Police Power in Vancouver, 1918-1939 - Russwurm, Lani (Simon Fraser University, 2007)
Policing in Vancouver was transformed by the labour unrest of the interwar period, culminating in a campaign carried out by a new civic regime that assumed power in response to a general strike threat. Complicating the process was that police workers were considered unreliable for policing labour disputes, especially since they unionized under the threat of a general strike in 1918. The challenge of “constituting authority” was therefore to render the police a reliable instrument against working class unrest. This study traces the development of policing through the postwar spate of waterfront strikes to the 1930s anticommunist campaign that carried the struggle into the political arena. Even as police power was being consolidated in the municipal police institution, rank and file police were undermined by tactics long used against other workers, namely labour spies and police specials. Like other workers, police resisted, modifying the process of change as a result.

The Stelco Saga: Restructuring and Resistance in the Neo-Liberal Era - Stone, Brendan (McMaster University, 2007)
Global market conditions have led to large corporate bankruptcies in recent years, particularly in the steel sector. Bankruptcy restructuring under the u.s. Chapter 11 or Canadian Companies' Creditors Arrangement Act [CCAA] places employee pensions at risk. In response to concessionary restructuring, the U.s. arm of the United Steelworkers [USW] intervened in several steel sector bankruptcies, developing restructuring solutions that led to partial or near-complete restoration of pensions and collective agreements. In Canada, during Stelco's troubled bankruptcy process between 2004 and 2006, Steelworker locals employed this interventionist method to prevent pension and collective agreement concessions. Scholars, such as Frost and Bacon, implicitly provide a rationale for union intervention into bankruptcy restructuring. They argue that union intervention in general corporate restructuring allows workers a greater voice in the process, leads to optimal results, and prevents union irrelevance. Frost outlines several criteria for maximizing union success during restructuring: the strength of union intra-organizational and external ties; the responsiveness of the union leadership towards the interests of the membership; and the ability of the union to access information and participate at all levels of the process. Many of Frost's recommendations were critical to the success of the USW locals at Stelco in achieving their bargaining and restructuring goals. Unlike in the more cooperative restructuring examples studied by Frost and Bacon, however, Stelco's Canadian locals employed a very assertive stance, since management exhibited initial hostility to union intervention. The union also found it necessary to enlist the help of government. While union intervention in bankruptcies remains a controversial process, it is one possible solution for troubled manufacturing unions, represents an overall USW push towards greater involvement in management, and may even lead towards an exit for labour from the discarded "post-war compromise."